Obtainment and Evaluation of Adjuvant Effect of the Aromatic Geranyl Derivative Filifolinone in Bacterin of Piscirickettsia Salmonis - Imarai-Bahamonde, C; Modak-Canobra, B; Valenzuela-Montenegro, B; Parra-Mardonez, N (Blackwell Publishing Ltd, 2018)
[No abstract available]